Peripheral NF-κB dysregulation in people with schizophrenia drives inflammation: putative anti-inflammatory functions of NF-κB kinases - Murphy, Caitlin E.; Walker, Adam K.; O’Donnell, Maryanne; Galletly, Cherrie; Lloyd, Andrew R.; Liu, Dennis; Weickert, Cynthia Shannon; Weickert, Thomas W. (Translational psychiatry, 2022)
Elevations in plasma levels of pro-inflammatory cytokines and C-reactive protein (CRP) in patient blood have been associated with impairments in cognitive abilities and more severe psychiatric symptoms in people with schizophrenia. The transcription factor nuclear factor kappa B (NF-κB) regulates the gene expression of pro-inflammatory factors whose protein products trigger CRP release. NF-κB activation pathway mRNAs are increased in the brain in schizophrenia and are strongly related to neuroinflammation. Thus, it is likely that this central immune regulator is also dysregulated in the blood and associated with cytokine and CRP levels. We measured levels of six pro-inflammatory cytokine mRNAs and 18 mRNAs encoding NF-κB pathway members in peripheral blood leukocytes from 87 people with schizophrenia and 83 healthy control subjects. We then assessed the relationships between the alterations in NF-κB pathway genes, pro-inflammatory cytokine and CRP levels, psychiatric symptoms and cognition in people with schizophrenia. IL-1β and IFN-γ mRNAs were increased in patients compared to controls (both p < 0.001), while IL-6, IL-8, IL-18, and TNF-α mRNAs did not differ. Recursive two-step cluster analysis revealed that high levels of IL-1β mRNA and high levels of plasma CRP defined ‘high inflammation’ individuals in our cohort, and a higher proportion of people with schizophrenia were identified as displaying ‘high inflammation’ compared to controls using this method ( p = 0.03). Overall, leukocyte expression of the NF-κB-activating receptors, TLR4 and TNFR2, and the NF-κB subunit, RelB, was increased in people with schizophrenia compared to healthy control subjects (all p < 0.01), while NF-κB-inducing kinase mRNAs IKKβ and NIK were downregulated in patients (all p < 0.05). We found that elevations in TLR4 and RelB appear more related to inflammatory status than to a diagnosis of schizophrenia, but changes in TNFR2 occur in both the high and low inflammation patients (but were exaggerated in high inflammation patients). Further, decreased leukocyte expression of IKKβ and NIK mRNAs was unique to high inflammation patients, which may represent schizophrenia-specific dysregulation of NF-κB that gives rise to peripheral inflammation in a subset of patients.